Aortic disease in Marfan syndrome is caused by overactivation of sGC-PRKG signaling by NO - Andrea de la Fuente-Alonso (Nature Communications, 2021)
Aortic aneurysm and dissection, the major problem linked to Marfan syndrome (MFS), lacks effective pharmacological treatment. Here, the authors show that the NO pathway is overactivated in MFS and that inhibition of guanylate cyclase and cGMP-dependent protein kinase reverts MFS aortopathy in mice.